Media and Moral Panic: Challenging LGBT in Minangkabau People 2016-2017 - Mufdil Tuhri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
Following the report of the existence of LGBT Group in Minangkabau society 2017, the local media, personal blog of public figures, official media social of local government, and several leaders of adat, religious leader, some civil societies responses assess to the new challenges for the decreasing of cultural and religious norm of Minangkabau people. The narrative has four stages: suggesting that the rejection of LGBT is against the cultural values of Minangkabau ethnic identity, reducing the social and adat (customary law) of Minangkabau people, considering LGBT is a threat and a social disease that affects the young generation of Minangkabau, and assuming LGBT is a form of decline for Islamic values that are considered embedding in the local tradition of society. This research argues that LGBT is a moral panic for the Minangkabau people produced by the power. This kind of moral panic emphasizes the disposition of the understanding of adat, religion and traditions around the public discourse. It means that this moral panic framework is a reproductive attempt to strengthen exclusive and conservatism trend in contemporary Minangkabau society and patriarchal influence which claim their attempts to maintain matrilineal values. To build on this argument, this paper will firstly present the context of heteronormativity in Indonesia and then discussing the context of Minangkabau people in West Sumatra.